Green Roof Ecosystems [electronic resource] - Sutton, Richard K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides an up-to-date coverage of green (vegetated) roof research, design, and management from an ecosystem perspective. It reviews, explains, and poses questions about monitoring, substrate, living components, and the abiotic, biotic, and cultural aspects connecting green roofs to the fields of community, landscape, and urban ecology. The work contains examples of green roof venues that demonstrate the focus, level of detail, and techniques needed to understand the structure, function, and impact of these novel ecosystems. Representing a seminal compilation of research and technical knowledge about green roof ecology and how functional attributes can be enhanced, it delves to explore the next wave of evolution in green technology and defines potential paths for technological advancement and research.
1. Introduction to Green Roof Ecosystems -- 2. Monitoring Abiotic Inputs and Outputs -- 3.Climates and Microclimates: Challenges for Extensive -- 4. Green Roof Design for Hot Climates -- 5. Water through Green Roofs -- 6. Nutrient Cycling in Green Roof Ecosystems -- 7. Soil-based Green Roofs -- 8. Bacteria and Fungi in Green Roof Ecosystems -- 9. Plant Biodiversity on Green Roofs -- 10. Effects of Vegetation on Green Roof -- 11. Ecosystem Services -- 12. Ruderal Green Roofs -- 13. Assembling Prairie Biome Plants for Minnesota -- 14. Green Roofs -- 15. Green Roof Plant Assemblage and Dynamics -- 16. Long-term Rooftop Plant Communities -- 17. Invertebrates on Green Roofs -- 18. Placing Green Roofs in Time and Space: Scale, Recruitment, Establishment, and Regeneration -- 19. Eco-regional Green Roof Case Studies -- 20. Green Roof Ecosystems: Summary and Synthesis.
Keywords: Life sciences; Regional planning; Urban planning